2018
DOI: 10.1021/acs.joc.8b01445
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistical Insights into the Bioconjugation Reaction of Triazolinediones with Tyrosine

Abstract: The bioconjugation at tyrosine residues using cyclic diazodicarboxamides, especially 4-substituted 3 H-1,2,4-triazole-3,5(4 H)-dione (PTAD), is a highly enabling synthetic reaction because it can be employed for orthogonal and site-selective (multi)functionalizations of native peptides and proteins. Despite its importance, the underlying mechanisms have not been thoroughly investigated. The reaction can proceed along four distinctive pathways: (i) the SAr path, (ii) along a pericyclic group transfer pathway (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Although TAD grafting to Tyr is generally described in the literature as an ene‐like reaction, an S E Ar mechanism most likely takes place (Figure 19). Indeed, the reaction shows higher conversion yields at basic pH, [82] probably because of higher phenolate reactivity in an S E Ar mechanism, as predicted by a recently published quantum chemical approach [83] …”
Section: Reactions With Triazolinedionesmentioning
confidence: 74%
See 1 more Smart Citation
“…Although TAD grafting to Tyr is generally described in the literature as an ene‐like reaction, an S E Ar mechanism most likely takes place (Figure 19). Indeed, the reaction shows higher conversion yields at basic pH, [82] probably because of higher phenolate reactivity in an S E Ar mechanism, as predicted by a recently published quantum chemical approach [83] …”
Section: Reactions With Triazolinedionesmentioning
confidence: 74%
“…Indeed, the reaction shows higher conversion yields at basic pH, [82] probably because of higher phenolate reactivity in an S E Ar mechanism, as predicted by a recently published quantum chemical approach. [83] The versatility of cyclic diazodicarboxamides for Tyr bioconjugation was first reported ten years ago by the Barbas' research group at the Scripps research institute. [82] Since then, published examples of successful phenyltriazolinedione (PTAD) conjugations have flourished, not only in the field of chemical biology but also in materials chemistry.…”
Section: Reactions With Triazolinedionesmentioning
confidence: 99%
“…We assessed the products of PTAD conjugation with tyrosine to determine products our experiment designs may produce. Previous reports noted such additional reactions as conjugates with amines, second additions to tyrosine phenols, and short-lived conjugations to cysteine residues 15,16 . We confirmed by 1 H NMR the reaction with a tyrosine analogue, 3-(4-hydroxyphenyl)propionic acid (Supplemental Spectra 1).…”
Section: Ptad Conjugation To Tyrosine or Peptides Can Yield Distinctimentioning
confidence: 97%
“…8,13 Herein we report the synthesis of protein nanocapsules that were crosslinked with a 4-phenyl-triazolinedione (TAD) derivative, which specifically reacts with amino acids with delocalized π-electron systems. [14][15][16][17] The ability of TAD to act as a strong dienophile in a Diels-Alder reaction has already been shown almost 60 years ago. 18 Recent studies performed by Du Prez and coworkers again showed its versatility in current applications in polymer science.…”
Section: Introductionmentioning
confidence: 99%